Cervical disk syndromes: value of metrizamide myelography and diskography. - Hartjes, H; Roosen, K; Grote, W; Buch, A; Brenner, A; Ruhnau, K; Hirche, H (American Journal of Neuroradiology, 1983)
This paper reports on the respective diagnostic values of myelography with water-soluble contrast media and diskography in a study of 100 patients examined between 1979 and 1981 and operated on because of cervical disk disease. The results of the study led to a change of the diagnostic procedures formerly applied in radicular syndromes (i.e., diskography, and then perhaps myelography) and in cervical myelopathy (myelography, rarely followed by diskography). Now cervical metrizamide myelography is always performed first. Diskography is only indicated in radicular syndromes to determine the segment causing clinical symptoms when there is a polysegmental space-occupying lesion on the myelogram in combination with a mono- or oligoradicular neurologic symptomatology; or in the case of a normal myelogram with complaints resistant to conservative treatment.